AB0616 The correlation between focus score and ultrasonography of major salivary glands in primary sjÖgren syndrome. (12th June 2018) - Sebastian, A.; Silicki, J.; Hałoń, A.; Wiland, P.
Abstract : Background: Currently, the role of salivary gland ultrasonography (SGUS) in the diagnosis of primary Sjögren's syndrome (pSS) is being determined. So far, in none of the proposed classification criteria for pSS SGUS is taken into consideration. The most recent analyses of patients show that SGUS can prove to be useful in the identification of even early forms of pSS. Objectives: We analized the SGUS changes in patients with pSS and its correlations with focus score (FS) of minor salivary glands and immunological and laboratory profile. Methods: We included 68 patients with pSS in the mean age of 51, based on the classification criteria from 2002. Results: In 33 (48%) patients were abnormal findings in major salivary glands detected (table 1). Scattered hypoechogenic changes of different size were the most common observed changes in SGUS, mainly in parotid glands. The FS was significantly higher in patients with changes in SGUS compare to the patients with normal images of major salivary glands (2.6 SD 1.3 vs 1.8 SD 1.2; p=0.02). In patients with SGUS abnormalities the hypergammaglobulinemia was most often observed (1.7 g/dl vs 1.2 g/dl; p=0.02). There was not the correlation between changes in major salivary glands and age (p=0.5), CRP value (p=0.1), ESR value (p=0.1), with blood cell count (p=0.1), rheumatoid factor (p=0.1), dry eye (p=01.), oral dryness (p=0.2), anty-SSA antibodies (p=0.5), anty-SSB antibodies (p=0.2), anty-Ro52 antibodies (p=0.4) observed. Conclusions: SGUS is a useful tool in patients with pSS. The abnormal images in SGUS of major salivary glands correlated with focus score of minor salivary glands and hypergammaglobulinemia but not with specific antibodies. Disclosure of Interest: None declared